Peran Pendidikan dalam Mewariskan Kebudayaan Sunda: Tinjauan Historis dan Strategis - Rivaldi, Mochamad Dzikri; Benhar, Dara Shaffira (Universitas Galuh, 2025)
This research examines the role of education as a custodian of Sundanese cultural heritage through historical approaches and cultural inheritance strategies. The phenomenon of the declining interest of the younger generation in Sundanese culture raises the urgency to examine how education can be an effective means of preserving and passing on these cultural values. This study reviews literature related to Sundanese education and culture, identifies gaps in the integration of formal and non-formal education in cultural inheritance, and offers novelty in the form of an adaptive inheritance strategy model. The methods used are historical and qualitative studies with documentation analysis and interviews. The results show that formal and informal education has an important role in maintaining and passing on Sundanese culture, but needs a more innovative and participatory strategy. The discussion highlights the importance of collaboration between educational institutions, communities and government in developing curriculum and cultural activities. The conclusion emphasizes education as the main guardian of Sundanese cultural heritage with recommendations to strengthen the cultural curriculum and actively involve the community in cultural heritage.